Double cystic duct - Dubhashi, Siddharth P.; Dubhashi, U.P.; Avnish, Aishwarya (International Surgery Journal, 2016)
Anatomical variations of the cystic duct may be encountered during cholecystectomy. Anatomical variations of cystic duct are known to occur in 18 to 23%. This is a case report of a female who underwent whipple’s procedure for a periampullary carcinoma. An H-type double cystic duct anomaly was an incidental finding. Surgeons must be aware of the possible extra-hepatic biliary anomalies to minimize the risk of complications.